2017
DOI: 10.1007/s11010-017-3242-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel intergenic miRNA located between the human DDC and COBL genes with a potential function in cell cycle arrest

Abstract: Frequent abnormalities in 7p12 locus in different tumors like lung cancer candidate this region for novel regulatory elements. MiRNAs as novel regulatory elements encoded within the human genome are potentially oncomiRs or miR suppressors. Here, we have used bioinformatics tools to search for the novel miRNAs embedded within human chromosome 7p12. A bona fide stem loop (named mirZa precursor) had the features of producing a real miRNA (named miRZa) which was detected through RT-qPCR following the overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Despite the great advances made in the field of RNA sequencing and related bioinformatics tools, novel functional RNA transcripts are still being added to the bank of RNA families . Relying on our previous successful discovery of novel miRNAs within important genes, we intended to search the GATA4 gene sequence for novel miRNA(s). Bioinformatics analysis suggested 90 stem‐loop structures within this genomic region, one of which, we named GATA4‐miR1 precursor, is located in the second intron of the gene and was chosen for further validations (Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great advances made in the field of RNA sequencing and related bioinformatics tools, novel functional RNA transcripts are still being added to the bank of RNA families . Relying on our previous successful discovery of novel miRNAs within important genes, we intended to search the GATA4 gene sequence for novel miRNA(s). Bioinformatics analysis suggested 90 stem‐loop structures within this genomic region, one of which, we named GATA4‐miR1 precursor, is located in the second intron of the gene and was chosen for further validations (Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four mRNAs (DDC, FGF9, GSG1, and LEFTY2) were considered to be significant for the overall survival of LUSC patients as verified by information from the GEO database. DDC, is a dopa deacidase, the expression of which is related to the biochemistry of many human cancers (Hoballa et al, 2018). Based on a number of previous studies, the expression of FGF9 showed carcinogenicity in human tumors (Hegab et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, there is nearly complete complementarity, which results in mRNA degradation and cleavage [ 18 , 19 ]. It has been shown that these molecules can act as oncogenes or tumor suppressors in cancers [ 20 , 21 ]. Moreover, miRNAs regulate cell differentiation, proliferation, and apoptosis by interacting with cancer target genes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%